Economic challenges of cloud computing in Iraqi educational institutions using exploratory analysis - Farah Hussein Mohammed Jawad; Huda Husein M. Jawad (Institute of Advanced Engineering and Science, 2021)
Cloud computing (CC) implementation for educational services is confronting several challenges. Prior research focused on the technological related challenges while few examine the economic challenges. The purpose of this study is to examine the economic challenges for using CC in educational institutions in Iraq. Articles pertaining to the topics were extracted from main databases. Based on the review, the critical challenges were identified. To confirm their relatedness to Iraqi context, a questionnaire related to the challenges was developed. A total of 204 respondents working as IT professional has participated in this study. The findings showed that the challenges mainly related to the infrastructure readiness, internet connection, cost of establishing and managing the CC. The challenges were divided into three phases. The pre-implementation phase includes the challenges of selecting service provider and deployment as well as the readiness of stakeholders, training, and infrastructure readiness. The implementation phase includes the challenges of maintaining the bandwidth, compatibility, legacy system, internet connection, reliability, availability, connectivity, and management. The post-implementation phase includes the challenges of security, privacy, quality of education, switching cost, and lock-in. The most critical challenges in all phases are related to infrastructure readiness, internet connection, switching cost and management of CC. The findings were discussed and limitations of the study as well as the direction for future works were given.